Three Dimensional Modeling of a Forested Area Using an Airborne Light Detection and Ranging Method - Soycan, Metin; Tunalioglu, Nursu; Ocalan, Taylan; Soycan, Arzu; Gumus, Kutalmis (SPRINGER HEIDELBERG, 2011)
Preserving forests and their value to us is indispensable to human life. When making forest preservation plans and managing forests efficiently, it is necessary to use three dimensional (3D) models of the forest regions. Apart from the traditional and photogrammetric methods used for producing these maps, the LIght Detection and Ranging (LIDAR) measurement technique with its various advantages has been used in recent years. This paper explains the principle of the operation of the LIDAR measurement system and discusses the determination of digital elevation models (DEM) of forest areas and their usage in 3D models. This test study aims to convert the scattered distributed 3D datasets obtained from airborne LIDAR technology to a digital elevation model with a regular grid format. One of the most significant aspects of this process, the interpolation method, which affects the quality of the final product when generating the digital elevation model, is examined with respect to data density and distribution, grid size interval and terrain type.
Keywords: LIDAR; Three dimensional modeling; Forestlands; Digital elevation model; Interpolation methods; DIGITAL ELEVATION MODELS; ACCURACY; PREDICTION; Science & Technology - Other Topics